2020
DOI: 10.1186/s40981-020-00340-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for post-induction hypotension in patients receiving 5-aminolevulinic acid: a single-center retrospective study

Abstract: Background 5-Aminolevulinic acid (5-ALA) is useful as a photodynamic agent, but its use commonly leads to hypotension. Although avoiding a mean arterial pressure (MAP) < 60 mmHg is important, the incidence of MAP < 60 mmHg when using 5-ALA is unclear. Therefore, we conducted a retrospective study to assess the incidence of post-induction hypotension and identified risk factors of this phenomenon. Methods One-hundred and seventy-two consecutive patients who underwent transurethral resection of the bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
2
19
1
Order By: Relevance
“…The correlation between intraoperative hypotension (SBP <80mmHg) and the use of antihypertensives was deemed significant (P = 0.015). Although general anesthesia may be a risk factor for 5-ALA-induced intraoperative hypotension (16) , (17) , the relation between intraoperative hypotension and anesthesia method was not significant in this study (P = 0.075).…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…The correlation between intraoperative hypotension (SBP <80mmHg) and the use of antihypertensives was deemed significant (P = 0.015). Although general anesthesia may be a risk factor for 5-ALA-induced intraoperative hypotension (16) , (17) , the relation between intraoperative hypotension and anesthesia method was not significant in this study (P = 0.075).…”
Section: Resultscontrasting
confidence: 71%
“…The method of anesthesia in urological surgery was significantly different between the 5-ALA-pretreated and non-pretreated patients. As previously reported, general anesthesia may be associated with 5-ALA-induced hypotension (16) , (17) . Thus, the method of anesthesia was added as an IPW variable in the urological surgery patients.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…To the Editor, 5-Aminolevulinic acid (ALA) is utilized for photodynamic diagnosis to detect superficial bladder cancer and its adverse effect is hypotension [1][2][3][4][5]. Compared to general anesthesia, spinal anesthesia is not indicated as an increased risk factor for 5-ALA-induced hypotension from anesthesia induction to the start of surgery in patients undergoing transurethral resection of bladder tumor (TUR-BT) with 5-ALA [2,3]. However, no studies exist that have investigated the precise perioperative hypotensive effects by 5-ALA under spinal anesthesia.…”
Section: Masami Sato * Tsutomu Yanagisawa Sonoko Minamino and Toshmentioning
confidence: 99%
“…Previous studies have reported the incidence of ALA-induced hypotension as 2–3% [ 9 , 10 ]. Cases of severe hypotension requiring intensive care management after using ALAGRIO® have been reported in Japan [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%